2019
DOI: 10.3390/su11216116
|View full text |Cite
|
Sign up to set email alerts
|

Integrating UAV Technology in an Ecological Monitoring System for Community Wildlife Management Areas in Tanzania

Abstract: Unmanned aerial vehicles (UAV) have recently emerged as a new remote sensing aerial platform, and they are seemingly advancing real-time data generation. Nonetheless, considerable uncertainties remain in the extent to which wildlife managers can integrate UAVs into ecological monitoring systems for wildlife and their habitats. In this review, we discuss the recent progress and gaps in UAV use in wildlife conservation and management. The review notes that there is scanty information on UAV use in ecological mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 76 publications
(146 reference statements)
0
18
0
Order By: Relevance
“…This study has revealed that using thermal drones in species detection for wildlife conservation based on machine learning approaches is promising due to its usefulness in generating high-quality data for the species population. Many conventional approaches for ecological surveys are challenging-that is, high costs and efforts, considerable time, highlevel observer skills required and inaccessibility to rugged areas [78]. Thermal imagery along with visual RGB bands provides high-quality predictors in detecting species in their habitats.…”
Section: Species Diversity and Detection Techniques From Thermal Photographs Of Two Large-sized Mammals In Baluran National Park (Bnp)mentioning
confidence: 99%
“…This study has revealed that using thermal drones in species detection for wildlife conservation based on machine learning approaches is promising due to its usefulness in generating high-quality data for the species population. Many conventional approaches for ecological surveys are challenging-that is, high costs and efforts, considerable time, highlevel observer skills required and inaccessibility to rugged areas [78]. Thermal imagery along with visual RGB bands provides high-quality predictors in detecting species in their habitats.…”
Section: Species Diversity and Detection Techniques From Thermal Photographs Of Two Large-sized Mammals In Baluran National Park (Bnp)mentioning
confidence: 99%
“…As another example of selecting an analysis target narrowed by the environment type, Verfuss et al [ 40 ] also reviewed RPAS applications for the detection and monitoring of marine fauna. Mangewa et al [ 41 ] analyzed previous studies applying the RPAS techniques to community wildlife management areas in Tanzania. Burke et al [ 42 ] focused on the optimization of RPAS-based thermal imaging strategies, considering the thermal effects of ground and atmosphere, occlusion by vegetation, and effective flight height for accurate image acquisition and identification of animals of interest.…”
Section: Introductionmentioning
confidence: 99%
“…One could perhaps deploy continuously recording cameras that do not have triggering mechanisms, but then again one runs into difficulties with obstacles to the field of view, massive data volumes and expensive computations, which are all drawbacks for real‐time monitoring. There are also promising new airborne methods emerging for real‐time monitoring by using drones (Mangewa et al., 2019), but they also have limitations such as field of view obstruction and environmental disruption due to noise.…”
Section: Introductionmentioning
confidence: 99%